Investigating news framing: a comparative study of media coverage on contemporary education issues in Malaysia - Chew, Chee Khiang; Fauziah Ahmad,; Faridah Ibrahim,; Chang, Peng Kee (Universiti Kebangsaan Malaysian, 2012)
This study examines how the Malay and Chinese language newspapers in Malaysia portray the issue of Teaching and Learning Science and Mathematics in English. Comparison was made between the two different language newspapers particularly in terms of framing by analyzing their coverage on two major incidents related to the issue – rally against the policy of Teaching and Learning Science and Mathematics in English (PPSMI), and the announcement of the Upholding the Malay Language, Strengthening Command of English policy (MBMMBI). This study uses the five generic frames developed by Semetko & Valkenburg (2000) as the basis of comparison. The five frames are responsibility, conflict, moral, economic consequences and human interest frame. The results suggest a congruency in the two different language newspapers reporting, which mainly emphasize the ‘conflict’ nature of the issue. However, a major difference in frame choice observed between the Malay and Chinese language newspapers in their reports of MBMMBI. While the prior significantly reduced the intensity of conflict frame in its reports on MBMMBI as compared to PPSMI, the latter maintain the same level of intensity for both the events.